[OP.5C.07] DO COMBINED ELECTROCARDIOGRAPHIC AND ECHOCARDIOGRAPHIC MARKERS OF LEFT VENTRICULAR HYPERTROPHY IMPROVE CARDIOVASCULAR RISK ESTIMATION?. (September 2016) - Cuspidi, C.; Seravalle, G.L.; Re, A.; Zanchettin, F.; Bonomi, F.; Trevano, F. Quarti; Facchetti, R.; Sala, C.; Bombelli, M.; Tadjc, M.; Mancia, G.; Grassi, G.
Abstract : Objective: We estimated the risk of cardiovascular mortality associated with echocardiographic (ECHO) sub-types of left ventricular hypertrophy (LVH), as defined by an up-dated classification, in subjects with and without electrocardiographic (ECG) LVH. To this purpose 1, 691 representatives of the general population of Monza, enrolled in the Pressioni Monitorate e Loro Associazioni (PAMELA) study, were included in the present analysis. Design and method: Cut-points for ECHO-LVH and abnormal LV geometry were derived from reference values of the healthy fraction of the PAMELA population by combining LV mass index, LV diameter and relative wall thickness, ECG-LVH was defined according to Cornell voltage index. Death certificates were collected over an average 211 months follow-up period. Results: A total of 89 fatal cardiovascular events were recorded during follow-up. Compared to individuals with neither ECHO-LVH nor ECG-LVH, fully adjusted risk of cardiovascular mortality increased (HR 3.36, 95% CI: 1.51-7.47, p = 0.003) in subjects with both ECHO- and ECG-LVH, whereas the risk entailed by ECHO-LVH alone was of borderline statistical significance (p = 0.04). Combined concentric LVH and ECG-LVH, but not concentric LVH alone, predicted the long-term incidence and risk of fatal cardiovascular events (HR = 3.78, 95% CI: 1.25–11.38, p = 0.01). Similar findings were observed for eccentric non dilated LVH. Conclusions: The present analysis underlines the value of combining ECG and ECHO in the assessment of cardiovascular prognosis related to LVH. The advantage of combining both noninvasive techniques in refining risk prediction persists also when echo-LVH is categorized according to concentric or eccentric LV patterns.